Interaction of p53 and ASPPs regulates rhesus monkey embryonic stem cells conversion to neural fate concomitant with apoptosis. Issue 9 (3rd May 2018) - Wang, Shuang; Yang, Lichuan; Bai, Raoxian; Ren, Shuaiwei; Niu, Yuyu; Ma, Yuanye; Ji, Weizhi; Chen, Yongchang
ABSTRACT: The tumor suppressor p53 is a key regulator of cell apoptosis and cell cycle arrest. Recent studies show that the delicate balance of p53 expression is important for neural tube defects, neuronal degeneration, embryonic lethality, as well as differentiation and dedifferentiation. Moreover, p53 showed different regulatory patterns between rodent and primate embryonic stem cells (ESCs). However, the role of p53 and apoptosis stimulating protein of p53 (ASPP) during neural differentiation (ND) from primate ESCs is still unknown. In this study, using an FGF-2 and/or HGF selectively containing ND culture systems for rhesus monkey ESCs (rESCs), the changes of p53 and ASPPs, and p53 targets, i.e. BAX and p21, were analyzed. Our results showed that the expression patterns of ASPP1/ASPP2 and iASPP were opposite in rESCs but similar in differentiated cells, and the expression of p53 was approximately consistent with BAX, but not p21. These findings indicate that the strong expression of iASPP in ESCs and weak expression of ASPP1/ASPP2 maintain the stability of stemness; and in ND niche, unimpaired iASPP may decrease its inhibition of ASPP1/ASPP2 expression, the interaction of p53 and ASPPs causing rESCs to convert towards a neural fate concomitant with apoptosis, but not to cell cycle arrest.